Past Scents : Historical Perspectives on Smell - Reinarz, Jonathan (Book collections on Project MUSE., 2014)
In this comprehensive and engaging volume, medical historian Jonathan Reinarz offers a historiography of smell from ancient to modern times. Synthesizing existing scholarship in the field, he shows how people have relied on their olfactory sense to understand and engage with both their immediate environments and wider corporal and spiritual worlds.